Thermodynamics and the destruction of resources - Bakshi, Bhavik R.; Gutowski, Timothy George Peter; Sekulić, Dušan P. (Cambridge University Press, 2011)
This book is a unique, multidisciplinary effort to apply rigorous thermodynamics fundamentals, a disciplined scholarly approach, to problems of sustainability, energy, and resource uses. Applying thermodynamic thinking to problems of sustainable behavior is a significant advantage in bringing order to ill-defined questions with a great variety of proposed solutions, some of which are more destructive than the original problem. The articles are pitched at a level accessible to advanced undergraduates and graduate students in courses on sustainability, sustainable engineering, industrial ecology, sustainable manufacturing, and green engineering. The timeliness of the topic, and the urgent need for solutions make this book attractive to general readers and specialist researchers as well. Top international figures from many disciplines, including engineers, ecologists, economists, physicists, chemists, policy experts and industrial ecologists among others make up the impressive list of contributors
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Power resources; Energy consumption; Conservation of natural resources; Thermodynamics; Erschöpfbare Ressourcen; Thermodynamik; Nachhaltigkeit